2012
DOI: 10.5897/ajb12.1497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of haematological and plasma biochemical effects of aqueous extracts of Parkia biglobosa seeds in rats

Abstract: The effects of sub-acute exposure to aqueous extract of Parkia biglobosa seeds on haematology and plasma biochemical parameters were studied. Twenty eight male Wistar albino rats were orally ingested with 0, 200, 400 and 800 mgkg -1 dose of the extract for 21 days and were sacrificed. Haematological parameters were assessed: red blood cell counts, haematocrit and haemoglobin concentration significantly (p<0.05) increased at the 800 mgkg -1 dose. We also observed significant increases in white blood cells, lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…However, the range of total protein in this study (4-7 g/100cm 3 ) fell within the range set by CACC. The concentration of total protein in this study was lower than that obtained by Ajibade, and Soetan (2012). This variance in the blood of rats might be attributed to the ingested herbal drug extracts.…”
Section: Biochemical Parameters Of Rats Ingested With the Selected Ancontrasting
confidence: 81%
See 1 more Smart Citation
“…However, the range of total protein in this study (4-7 g/100cm 3 ) fell within the range set by CACC. The concentration of total protein in this study was lower than that obtained by Ajibade, and Soetan (2012). This variance in the blood of rats might be attributed to the ingested herbal drug extracts.…”
Section: Biochemical Parameters Of Rats Ingested With the Selected Ancontrasting
confidence: 81%
“…The slightly higher concentration of total protein in the blood of test rats compared to the rats in the control groups but the values fell within normal limits. They might be due to the fact that the medicinal plants from which the herbal drugs are made are rich in protein, which may increase the amount of protein in the diet, and thus in the blood, Ajibade, and Soetan (2012). This suggests that these herbal drugs possess good nutritional value.…”
Section: Biochemical Parameters Of Rats Ingested With the Selected Anmentioning
confidence: 99%
“…Therefore, the assessment of haematological parameters is also useful to determine the extent of deleterious/favourable effects of foreign compounds on immune response related cells. A rise or fall in the haematological parameters may vary the immune constitution of the body, thereby affecting the health [64,65] . Differential count of WBCs; total count of WBCs and erythrocytes and also platelet counts were done from the blood samples collected from various control and treated groups.…”
Section: Resultsmentioning
confidence: 99%
“…The hematological parameters were assessed for any variation indicating the modulation in the immune responses and to determine the detrimental and beneficial effects of foreign materials on immune cells ( Ajibade and Soetan, 2012 ). In this study, we observed that, most of the haematological parameters (Hb level, DLC, TLC, RBC, platelet count) were significantly decreased in all groups after CP-administration to mice.…”
Section: Discussionmentioning
confidence: 99%